2013
DOI: 10.1007/s12630-013-9922-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated cor triatriatum sinistrum and pregnancy: case report and review of the literature

Abstract: Purpose Isolated cor triatriatum sinistrum (CTS) is a heart malformation in which a perforated fibromuscular membrane divides the left atrium into two chambers. When communication between these chambers is restricted, a patient may have signs and symptoms of mitral stenosis. The later stages of pregnancy are associated with tachycardia and increases in intravascular volume. We describe how this altered physiology may affect pregnant women with asymptomatic CTS. We also review the literature relating to pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In two patients, the diagnosis was established by autopsy 8 9. CTS was diagnosed during pregnancy in 10 patients10–19 and in 1 after successful labour 20. Obstructive membrane physiology was reported in 70 (41%) patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In two patients, the diagnosis was established by autopsy 8 9. CTS was diagnosed during pregnancy in 10 patients10–19 and in 1 after successful labour 20. Obstructive membrane physiology was reported in 70 (41%) patients.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas CTS in paediatric patients rarely is an incidental finding,29–33 40 this accounts for one of four adult patients with the non-obstructive membrane 15 17 21 47–4929.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[20][21][22][23][24][25][26][27] In these women the aperture across the accessory atrial membrane, adequate for a pre-pregnancy hemodynamic state, may become inadequate to accommodate large physiologic increases in hemodynamics associate with uterine autotransfusion after delivery. [28] Pre-operative treatments Dependent on presenting symptomatology of CT, a corrective surgery or rarely percutaneous balloon dilatation of intra-atrial aperture [29] may be indicated before major elective surgery. Pre-operatively, all symptomatic patients with CT should be medically treated and special emphasis should be placed on controlling of the fast ventricular rate to promote adequate diastolic filling.…”
Section: Discussionmentioning
confidence: 99%
“…48 Pregnancy and postpartum period induced hyperdynamic circulation precipitate symptomatology. 47,[49][50][51][52][53] The proximal chamber dilates similar to the left atrium as in mitral stenosis and, therefore, becomes a nidus for atrial arrhythmia and the harbinger of thrombus and ectopic foci resulting in cerebral and systemic embolic events. [54][55][56][57][58][59] Chronic anticoagulation therapy is mandatory in such circumstances.…”
Section: Symptomatologymentioning
confidence: 99%